Seventy Years of Chlamydia Vaccine Research – Limitations of the Past and Directions for the Future - Phillips, Samuel; Quigley, Bonnie L.; Timms, Peter (Frontiers in Microbiology, 2019)
Chlamydia is a major bacterial pathogen that infects humans, as well as a wide range of animals, including marsupials, birds, cats, pigs, cattle, and sheep. Antibiotics are the only treatment currently available, however, with high rates of re-infection, there is mounting pressure to develop Chlamydia vaccines. In this review, we analyzed how Chlamydia vaccine trials have developed over the past 70 years and identified where future trials need to be focused. There has been a strong bias toward studies targeting C. muridarum and C. trachomatis within mice and a lack of studies matching chlamydial species to their end target host. Even though a large number of specific antigenic targets have been studied, the results from whole-cell vaccine targets show slightly more promising results overall. There has also been a strong bias toward systemic vaccine delivery systems, despite the finding that mucosal delivery systems have shown more promising outcomes. However, the only successful vaccines with matched chlamydial species/infecting host are based on systemic vaccine delivery methods. We highlight the extensive work done with mouse model trials and indicate that whole cell antigenic targets are capable of inducing an effective response, protecting from disease and reducing shedding rates. However, replication of these results using antigen preparations more conducive to commercial vaccine production has proven difficult. To date, the Major Outer Membrane Protein (MOMP) has emerged as the most suitable substitute for whole cell targets and its delivery as a combined systemic and mucosal vaccine is most effective. Finally, although mouse model trials are useful, differences between hosts and infecting chlamydial strains are preventing vaccine formulations from mouse models to be translated into larger animals or intended hosts.